2016
DOI: 10.1038/sigtrans.2016.25
|View full text |Cite|
|
Sign up to set email alerts
|

A novel cancer vaccine with the ability to simultaneously produce anti-PD-1 antibody and GM-CSF in cancer cells and enhance Th1-biased antitumor immunity

Abstract: Tumor escape from immune-mediated destruction has been associated with immunosuppressive mechanisms that inhibit T-cell activation. A promising strategy for cancer immunotherapy is to disrupt key pathways regulating immune tolerance, such as program death-1 (PD-1/PD-L1) pathway in the tumor environment. However, the determinants of response to anti-PD-1 monoclonal antibodies (mAbs) treatment remain incompletely understood. In murine models, PD-1 blockade alone fails to induce effective immune responses to poor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 47 publications
3
25
0
Order By: Relevance
“…Furthermore, the results of flow cytometry showed that the vaccine increased the proportion of CD4+ T and CD8+ T cells in the spleen and TME, suggesting the important role of CD4+ T and CD8+ T cells in antitumor immunity. Consistent with our results, Tondini et al and Tian et al evaluated CD4+ T and CD8+ T cells in vivo by injecting anti-CD4 and anti-CD8 antibodies in mice, and found that tumor regression was dependent on CD4+ T and CD8+ T cells [ 25 , 26 , 27 ]. Other experiments have also shown that increases in the numbers of CD4+ T and CD8+ T cells in the TME are closely related to tumor prognosis [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the results of flow cytometry showed that the vaccine increased the proportion of CD4+ T and CD8+ T cells in the spleen and TME, suggesting the important role of CD4+ T and CD8+ T cells in antitumor immunity. Consistent with our results, Tondini et al and Tian et al evaluated CD4+ T and CD8+ T cells in vivo by injecting anti-CD4 and anti-CD8 antibodies in mice, and found that tumor regression was dependent on CD4+ T and CD8+ T cells [ 25 , 26 , 27 ]. Other experiments have also shown that increases in the numbers of CD4+ T and CD8+ T cells in the TME are closely related to tumor prognosis [ 28 , 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…Alternatively, given the success of PD-1/PD-L1 blocking antibodies in human cancer, incorporating existing devil PD-1/PD-L1 blocking antibodies in immunotherapies and vaccines could be an effective means to amplify anti-DFT responses. Another potential approach that can be explored with the system developed here is to modify the tumor cells to produce the blocking antibodies (39). This would actually be more cost-effective than using purified antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the proteins/peptides approach, genetic vaccines (either DNA- or RNA-based) can deliver large chunks of antigenic information into target cells, making it possible to induce the expression of multiple TAAs with a single immunization [38,55,57,58,59]. Furthermore, with a suitable choice of a genetic vaccine and a vector, it is possible to induce ectopic TAAs expression not only on cancer cells, but also, and possibly concomitantly, on the DCs which are needed to elicit complete T cell activation [55,60,61], thus resulting in cross-priming and/or direct antigen presentation and large benefits in terms of response magnitude.…”
Section: Tumor Immune Microenvironmentmentioning
confidence: 99%